Strategies for improving expression of recombinant human chorionic gonadotropin in Chinese Hamster Ovary (CHO) cells - Boukari, Iheb; Rourou, Samia; Bouzazi, Dorsaf; Essafi-Benkhadir, Khadija; Kallel, Héla (Protein expression and purification, 2025)
Optimizations of the gene expression cassette combined with the selection of an appropriate signal peptide are important factors that must be considered to enhance heterologous protein expression in Chinese Hamster Ovary (CHO) cells. In this study, we investigated the effectiveness of different signal peptides on the production of recombinant human chorionic gonadotropin (r-hCG) in CHO-K1 cells. Four optimized expression constructs containing four promising signal peptides were stably transfected into CHO-K1 cells. The generated CHO-K1 stable pool was then evaluated for r-hCG protein production. Interestingly, human serum albumin and human interleukin-2 signal peptides exhibited relatively greater extracellular secretion of the r-hCG with an average yield of (16.59 ± 0.02 μg/ml) and (14.80 ± 0.13 μg/ml) respectively compared to the native and murine IgGκ light chain signal peptides. The stably transfected CHO pool was further used as the cell substrate to develop an optimized upstream process followed by a downstream phase of the r-hCG. Finally, the biological activity of the purified r-hCG was assessed using in vitro bioassays. The combined data highlight that the choice of signal peptide can be imperative to ensure an optimal secretion of a recombinant protein in CHO cells. In addition, the stable pool technology was a viable approach for the production of biologically active r-hCG at a research scale with acceptable bioprocess performances and consistent product quality. •We developed a highly efficient approach for producing recombinant human chorionic gonadotropin (r-hCG) in CHO cells.•We highlighted the importance of selecting an appropriate signal peptide for enhancing r-hCG expression in CHO cells.•Stable pool technology yields high-quality, biologically active r-hCG at the research scale, ensuring efficiency and consistent performance.